ANALISIS KORESPONDENSI UNTUK MENDAPATKAN PETA PERSEPSI DAN VARIABEL BAGI KEGIATAN USAHA (Studi Kasus Rumah Makan Spesial Sambal (SS) terhadap Pesaingnya) - Susi Ekawati; Agus Rusgiyono; Triastuti Wuryandari (Jurnal Gaussian, 2015)
Correspondence analysis is a technique for displaying the rows and columns of a data matrix primarily, a two-way contingency table as points in dual low-dimensional vector spaces. This technique is used to reduce the dimension of variables and describe the profile vector of rows and columns of the contingency table. This research aims to determine the position of the rivalry between the restaurants in Tembalang region based on consumer’s perceptions and to identify variables that distinguish it. The variables which used are including the price, taste, cleanliness, service, variety of food, and parking lots. Correspondence analysis is used to determine the variables that distinguish the 5th of the restaurant. The correspondence analysis produces a combined perceptual map with the satisfaction variables restaurant. From the analysis, it can be concluded that the perceptual map in the correspondence analysis shows the proximity between restaurant and satisfaction variables. Keywords : correspondence analysis, perceptual map, restaurant, satisfaction.